2012
DOI: 10.5858/arpa.2011-0113-oa
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Relevance of Unsatisfactory and Satisfactory but Limited Smears of Liquid-Based Compared With Conventional Cervical Cytology

Abstract: N Context.-Recent randomized controlled trials have shown a significant decrease in unsatisfactory rates for liquid-based cytology (LBC) compared with conventional Papanicolaou test (CP). The underlying causes and relevance of unsatisfactory results for LBC and CP have never been compared within the setting of a randomized controlled trial.Objective.-To examine differences in causes and relevance of unsatisfactory and satisfactory but limited by (SBLB) results for LBC and CP.Design.-Data from the Netherlands T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 24 publications
2
18
0
4
Order By: Relevance
“…This is consistent with a previous study concluding that LBC eliminates most sources of unsatisfactory tests with the exception of scant cellularity, which is the main reason for unsatisfactory LBC tests [23]. In particular, obscuring factors, which were the cause of a large proportion of the unsatisfactory CS test results, were found to be less frequent in the LBC method.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with a previous study concluding that LBC eliminates most sources of unsatisfactory tests with the exception of scant cellularity, which is the main reason for unsatisfactory LBC tests [23]. In particular, obscuring factors, which were the cause of a large proportion of the unsatisfactory CS test results, were found to be less frequent in the LBC method.…”
Section: Discussionsupporting
confidence: 92%
“…The studies done by Siebers et al [19] and Gupta N et al [17] found scant cellularity as the sole cause for unsatisfactory LBC, similar to our study.…”
Section: Discussionsupporting
confidence: 92%
“…44,45 Now that most U.S. cytology is done using liquid-based media, which can control for most obscuring factors in processing, unsatisfactory results arise largely from insufficient squamous cells. 46 Evidence is sparse governing management of women with unsatisfactory cytology obtained as part of co-testing, although risk for high-grade disease in women with negative HPV tests appears to be low. 47 Unsatisfactory results arise largely from insufficient squamous cells.…”
Section: Management Of Abnormal Screening Tests Unsatisfactory Cytologymentioning
confidence: 99%